2013
DOI: 10.1038/ncomms3501
|View full text |Cite
|
Sign up to set email alerts
|

Species differences and molecular determinant of TRPA1 cold sensitivity

Abstract: TRPA1 is an ion channel and has been proposed as a thermosensor across species. In invertebrate and ancestral vertebrates such as fly, mosquito, frog, lizard and snakes, TRPA1 serves as a heat receptor, a sensory input utilized for heat avoidance or infrared detection. However, in mammals, whether TRPA1 is a receptor for noxious cold is highly controversial, as channel activation by cold was observed by some groups but disputed by others. Here we attribute the discrepancy to species differences. We show that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
191
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 207 publications
(205 citation statements)
references
References 40 publications
8
191
2
2
Order By: Relevance
“…2010; Chen et al. 2013). The rodent findings suggest that inhibiting abnormal small‐diameter primary afferent activity could be useful in the treatment of oxaliplatin‐induced neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2010; Chen et al. 2013). The rodent findings suggest that inhibiting abnormal small‐diameter primary afferent activity could be useful in the treatment of oxaliplatin‐induced neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…2011; Chen et al. 2013; Hirai and Hama 2014). The species difference in molecular biology could be one reason for the disconnection between significant efficacy observed in rodent models of oxaliplatin‐induced neuropathic pain and the failure to replicate efficacy in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations on the temperature sensitivity of TRPA1 across different species (46) have indeed shown that the temperature sensitivity of TRPA1 could be species-dependent, as a result of an evolutionary divergence driven by different requirements for survival (189).…”
Section: Noxious Cold Transductionmentioning
confidence: 99%
“…In their recent work, Chen et al (46) have shown that the TRPA1 ion channel can alternatively be a heat sensitive channel in invertebrates and ancestral invertebrates (e.g. fly and snakes), a noxious cold sensitive channel in rat and mouse, and a temperature insensitive channel in human and rhesus monkey.…”
Section: Noxious Cold Transductionmentioning
confidence: 99%